Effects of different proteases on the emulsifying capacity, rheological and structure characteristics of preserved egg white hydrolysates. (February 2019) - Ai, Minmin; Tang, Ting; Zhou, Ledan; Ling, Ziting; Guo, Shanguang; Jiang, Aimin
Abstract: This paper investigated the effects of six proteases on the properties of preserved egg white gel, including emulsifying capacity, rheological properties and intermolecular interactions. The results showed that the hydrolysis degree (DH) and nitrogen solubility index (NSI) of preserved egg white gel hydrolysates increased, and the surface hydrophobicity declined due to the embedding and destruction of the hydrophobic groups. The determination of zeta potential and particle size indicated that the hydrolysate peptides treated by flavourzyme occurred to aggregation to exhibit a larger particle size in contrast to other proteases. The emulsifying ability of preserved egg white hydrolysates dropped after the hydrolysis of proteases, except the flavourzyme at pH 3.0, 5.0, and 7.0, and the emulsifying stability declined obviously, in addition to the pepsin at pH 5.0 and 7.0 and the neutrase at pH 9.0, which were similar to the results of rheological characteristics determined by rheometer. Additionally, the enzymatic hydrolysis caused significant increase in the total sulfhydryl and disulfide bond contents of hydrolysates compared with those of the untreated preserved egg white. The results of intermolecular interactions and Fourier transform infrared spectrometry (FTIR) indicated that preserved egg white hydrolysates were mainly supported by the hydrogen bonds and hydrophobic interactions. These results suggested that the hydrolysates of preserved egg white possessed different physicochemical and functional characteristics, which were attributed to the different effects of six proteases on the structure of preserved egg white proteins. Graphical abstract: Image 1 Highlights: Six proteases were employed to hydrolyse preserved egg white. Flavourzyme hydrolyzed samples more thoroughly, but peptide aggregation occurred. The emulsifying capacity of most proteases hydrolysates was reduced. Hydrogen bond and hydrophobic interaction were the main supporting molecule forces.